1977
DOI: 10.1287/mnsc.24.2.235
|View full text |Cite
|
Sign up to set email alerts
|

Note—A Note on “Comparison of Computer Algorithms and Visual Based Methods for Plant Layout” by M. Scriabin and R. C. Vergin

Abstract: Please scroll down for article-it is on subsequent pages With 12,500 members from nearly 90 countries, INFORMS is the largest international association of operations research (O.R.) and analytics professionals and students. INFORMS provides unique networking and learning opportunities for individual professionals, and organizations of all types and sizes, to better understand and use O.R. and analytics tools and methods to transform strategic visions and achieve better outcomes. For more information on INFORMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…CRAFT was able to obtain a twelve percent improvement in the cost of the 135 % flow dominance problem, but was much less effective in the other three problems, they concluded that layout problems having flow matrix data with a coefficient of variatism in excess of 200 % can probably be solved by inspection of the flow matrix or some other approximation techm.que, while those with lower flow would benefit from a computer approach. This 200 % limit has subsequently been regarded as valid by some authors (Block ( 1977), Buffa ( 1976b) and has been partially or completely rejected by others (Scriabin and Vergin 1981 for the 10-facility problem we obtained a value of 201.7% comparable to the 201 %reported by Vollmann and Buffa (1966), while the 20-facility problem yielded a flow dominance of 251.2% comparable to the reported 252 %. (We were unable tq check the reported flow dominance of 519% for the 22-facility problem, since the paper by Buffa, Armour and Vollmann (1964) only gives a partial extract of the original flow matrix).…”
Section: The Flow Dominance Conceptmentioning
confidence: 49%
See 2 more Smart Citations
“…CRAFT was able to obtain a twelve percent improvement in the cost of the 135 % flow dominance problem, but was much less effective in the other three problems, they concluded that layout problems having flow matrix data with a coefficient of variatism in excess of 200 % can probably be solved by inspection of the flow matrix or some other approximation techm.que, while those with lower flow would benefit from a computer approach. This 200 % limit has subsequently been regarded as valid by some authors (Block ( 1977), Buffa ( 1976b) and has been partially or completely rejected by others (Scriabin and Vergin 1981 for the 10-facility problem we obtained a value of 201.7% comparable to the 201 %reported by Vollmann and Buffa (1966), while the 20-facility problem yielded a flow dominance of 251.2% comparable to the reported 252 %. (We were unable tq check the reported flow dominance of 519% for the 22-facility problem, since the paper by Buffa, Armour and Vollmann (1964) only gives a partial extract of the original flow matrix).…”
Section: The Flow Dominance Conceptmentioning
confidence: 49%
“…Vollmann and Buffa (1966) conducted a computational experiment on four example layout problems which, in comb th the reported flow dominance values, paved the way for many confusing and utmost conflicting papers, replies and rejoinders on the potential use of flow dominance and some derived complexity measures to determine the choice between computer algorithms and visual based layout methods (Block ( 1977(Block ( , 1979. Buffa' (1976b), Coleman (1977Coleman ( ), S and (1975Coleman ( , 1976Coleman ( , 1981, Trybus and Hopkins (1980)).…”
Section: The Flow Dominance Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…Coleman [12] added his reservations about the results. Block [13] showed that more research should be carried out. Sometimes it would be necessary to uncover the hidden pattern of the flow characteristics and use this to help to determine the layout.…”
Section: Searching For a Solutionmentioning
confidence: 99%
“…During the 1970s and 1980s, operations research and management science specialists were particularly interested in comparing the performances of human subjects to computer algorithms on a type of quadratic assignment problem related to the location of departments within a facility (Block, 1977;Coleman, 1977;Herroelen & Van Gils, 1985;Scriabin & Vergin, 1975;Trybus & Hopkins, 1980). Subjects were provided with information regarding the flow (or interaction) between each pair of q departments, which enabled them to place pairs of departments with high interactions close to one another in the layout.…”
Section: Introductionmentioning
confidence: 99%